The Erosion of Borderless Norden? Practices and Discourses on Nordic Border Restrictions in Finland and Sweden during the Covid-19 Pandemic - Heinikoski Saila; Hyttinen Tatu (Utrecht University School of Law, 2022)
Nordic countries are part of the borderless Schengen Area, but free movement in the Nordic countries, or Norden, dates back even further: no border controls or restrictions on workers' movements have existed since the entry into force of the Nordic labour market and passport union in 1958. This article outlines how Finland and its neighbour Sweden, the only Nordic country to keep borders open for Finland in 2020, approached closed borders in Norden during the Covid-19 pandemic, when free movement of Nordic citizens was suspended for the first time in almost 70 years, to be restored only in summer 2021. The article examines the Finnish and Swedish border practices and political debates. Parliamentary discourses are analysed from the perspective of two ideal types of argumentation, namely utilitarian and deontological, arguing that the suspension of free movement leaves long-lasting scars in the trust of both politicians and citizens in interaction across borders.